2008
DOI: 10.1186/1757-1626-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Incidental pheochromocytoma presenting with sublaboratory findings in asymptomatic surrenal masses: a case report

Abstract: Introduction: Adrenal incidentaloma can be described as adrenal lesions that are incidentally diagnosed during abdominal laparotomy or any abdominal screening without prior suspicion of adrenal disease. It is important to diagnose adrenal lesions to learn if they are hormonally active or malignant. The most common clinical sign of pheochromocytoma is sustained or paroxysmal hypertension, and the most common symptoms are headache, excessive truncal sweating, and palpitation. In some cases, the clinical symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Although reported, completely "silent", hormonally inactive, very large and assumably old pheochromocytomas are very rare (1,30,31).…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although reported, completely "silent", hormonally inactive, very large and assumably old pheochromocytomas are very rare (1,30,31).…”
Section: Measurementsmentioning
confidence: 99%
“…Due to technological advances the frequency of AI diagnosis increased about 20 times in the last three decades (1). According to autopsy data the incidence of these lesions is age dependent, being 1% of people at age 30, 3% of people older than 50 years of age and 7% at age 70, without difference in gender (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While marker‐negative pheochromocytomas represent a small subset of an already rare tumor, they are not uncommon, and warrant a high level of clinical suspicion in a patient who presents with adrenal incidentaloma. There is little information in the current literature concerning the prevalence and nature of marker‐negative pheochromocytomas, with the majority being case studies of single patients . The primary objective of this analysis was to compare patient characteristics and clinical presentation between marker‐positive and marker‐negative pheochromocytomas.…”
Section: Introductionmentioning
confidence: 99%
“…However, many case reports have shown that urine catecholamines are normal [22,23]. Ozkaya et al [24] reported a case that …”
Section: Discussionmentioning
confidence: 99%